Localisation and distance between ABL and BCR genes in interphase nuclei of bone marrow cells of control donors and patients with chronic myeloid leukaemia - Lukásová, E; Kozubek, S; Kozubek, M; Kjeronská, J; Rýznar, L; Horáková, J; Krahulcová, E; Horneck, G (Human genetics, 1997)
Quantitative measurements of the nuclear localisation of the ABL and BCR genes and the distance between them were performed in randomly oriented bone marrow cells of control donors and patients with chronic myeloid leukaemia (CML). Most ABL and BCR genes (75%) are located at a distance of 20-65% of the local radius from the nuclear centre to the nuclear membrane. A chimeric BCR-ABL gene located on a derivative chromosome 22 resulting from t(9;22)(q34;q11) [the so-called Philadelphia (Ph) chromosome] as well as the intact ABL and BCR genes of patients suffering from chronic myeloid leukaemia are also located mostly in this region, which has a mean thickness of 2 microns in bone marrow cells. We have not found any significant differences in the location of the two genes in the G1 and G2 phases of the cell cycle, nor between bone marrow cells and stimulated lymphocytes. Irradiation of lymphocytes with a dose of 5 Gy of gamma-rays results in a shift of both genes to the central region of the nucleus (0-20% of the radius distant from the nuclear centre) in about 15% of the cells. The minimum distance between one ABL and one BCR gene is less than 1 micron in 47.5% of bone marrow cells of control donors. Such a small distance is found between homologous ABL and between homologous BCR genes in only 8.1% and 8.4% of cells, respectively. It is possible that the relative closeness of nonhomologous ABL and BCR genes in interphase nuclei of bone marrow cells could facilitate translocation between these genes. In 16.4% of bone marrow cells one ABL and one BCR gene are juxtaposed (the distance between them varies from 0-0.5 micron) and simulate the Ph chromosome. This juxtaposition is the result of the projection of two genes located one above another into a plane, as follows from the probability calculation.
Keywords: bcr-abl fúzní proteiny; DNA Probes; Fusion Proteins, bcr-abl; Genes, abl; Male; Philadelphia Chromosome; Cell Nucleus; tyrosinkinasy; hybridizace in situ fluorescenční; chronická myeloidní leukemie; buňky kostní dřeně; Proto-Oncogene Proteins; DNA nádorová; Adult; Proto-Oncogenes; Image Processing, Computer-Assisted; dospělí; mužské pohlaví; buněčné jádro; lymfocyty; Gamma Rays; Interphase; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; protoonkogeny; DNA, Neoplasm; interfáze; počítačové zpracování obrazu; Proto-Oncogene Proteins c-bcr; lidé; geny abl; ženské pohlaví; Humans; Lymphocytes; DNA sondy; In Situ Hybridization, Fluorescence; filadelfský chromozom; Female; Protein-Tyrosine Kinases; protoonkogenní proteiny c-bcr; záření gama; lidé středního věku; Bone Marrow Cells; protoonkogenní proteiny; Middle Aged